Characteristics and properties of nitrocellulose/glycidyl azide polymer/2, 4, 6, 8, 10, 12-hexanitro-2, 4, 6, 8, 10, 12-hexaazaisowurtzitane nanocomposites synthesized using a sol–gel supercritical method. (24th January 2019) - Wang, Yi; Zhang, Mi; Song, Xiaolan; Huang, Hao; Li, Fengsheng
Nitrocellulose/glycidyl azide polymer/2, 4, 6, 8, 10, 12-hexanitro-2, 4, 6, 8, 10, 12-hexaazaisowurtzitane nanocomposites, in which 2, 4, 6, 8, 10, 12-hexanitro-2, 4, 6, 8, 10, 12-hexaazaisowurtzitane nanoparticles uniformly embedded in nitrocellulose/glycidyl azide polymer matrix, were synthesized using a sol–gel supercritical method. The micron morphology, crystal phase, molecular structure, specific surface area, and surface elements were characterized using scanning electron microscopy, X-ray diffractometry, infrared, Brunauer–Emmett–Teller, and X-ray photoelectron spectroscopy analyses, respectively. Thermal analyses were performed, and the kinetic and thermodynamic parameters, such as activation energy, per-exponent factor, rate constant, activation heat, activation free energy, and activation entropy, were calculated. The decomposition products of the nitrocellulose/glycidyl azide polymer matrix and nitrocellulose/glycidyl azide polymer/2, 4, 6, 8, 10, 12-hexanitro-2, 4, 6, 8, 10, 12-hexaazaisowurtzitane were also investigated by differential scanning calorimetry–infrared analysis. The result indicated that the main decomposition product of nitrocellulose/glycidyl azide polymer is carbon dioxide and the –N3 group in glycidyl azide polymer decomposed to nitrogen without being detected by infrared spectrometer; the main decomposition products of nitrocellulose/glycidyl azide polymer/2, 4, 6, 8, 10, 12-hexanitro-2, 4, 6, 8, 10, 12-hexaazaisowurtzitane are carbon dioxide, nitrous oxide, and water, and few carbon monoxide, methane, and nitrogen oxide are also detected. Energy performances of nitrocellulose/glycidyl azide polymer matrix and nitrocellulose/glycidyl azide polymer/2, 4, 6, 8, 10, 12-hexanitro-2, 4, 6, 8, 10, 12-hexaazaisowurtzitane nanocomposites were evaluated, that is, the parameters such as standard specific impulse, characteristic speed, combustion chamber temperature, average molecular weight of combustion products, and explosion heat were calculated. The results illustrated that as the weight percentage of nitrocellulose increases, the values of standard specific impulse, characteristic speed, average molecular weight of combustion products, combustion chamber temperature, and explosion heat increase. This was ascribed to that the oxygen balance of glycidyl azide polymer is substantially lower than that of nitrocellulose, which results in that the chemical energy of glycidyl azide polymer does not release sufficiently. Additionally, as weight percentage of glycidyl azide polymer increases, the impact and friction sensitivity of the composites decrease obviously. This means that glycidyl azide polymer is much more insensitive than nitrocellulose.